Representations of anorexia in an EAP classroom: critically engaging with the body and its discourses. Issue 2 (2nd April 2020) - Chun, Christian W.
ABSTRACT: Aside from mentioning possible issues of hidden identities and curriculum development relating to anorexia, little research has been done exploring how discourses of eating disorders and images of the body have been mediated by teachers and learners in the English for Academic Purposes (EAP) classroom. Drawing upon an ethnographic EAP classroom case study, this article explores how particular meanings of anorexia were framed, discussed, and challenged in this classroom context by an instructor and her students engaged with discourses surrounding eating disorders in a YouTube video, Anorexia: The 10 Most Common Misconceptions about Eating Disorders . I employ a mediated discourse nexus analysis approach to examine the ways in which the teacher and her students differentiated between facts and opinions presented in the video, and the critical engagements with the various representations of eating disorders and the accompanying discourses of the body in different societies.